(untitled) (Global Journal of Human-Social Science, 2022)
Municipal water utilities across the state provide intermittent water services IWS with frequencies ranging from daily to weekly deliveries To expand supplies increase coverage and improve services municipal bodies are looking for alternative ways to fund drinking water services Public-Private Partnerships PPP are one of the means being explored by many municipal bodies to attract private investment in the water sector In 2008 under a loan from the World Bank as part of a scheme administered by the state of Karnataka Hubli-Dharwad upgraded eight wards as a demonstration project demo wards to continuous water services CWS Hubli-Dharwad upgraded an additional 18 wards to CWS in 2015 extension wards and has plans to scale up CWS to all remaining wards shortly In this background we tried to understand the ongoing affordability issues and water scarcity challenges in the scale-up of CWS as compared to demo zones of CWS and to discourse on sustenance issues regarding the management and provision of urban water supply including planning the role of the public and private sector involvement of stakeholders availability of water their sources networking financing and maintenance in India Out of 67 wards we selected 28 and collected information from 840 households